HUNTER, PEASANT, REBEL - Baruah, Manjeet. Link ([S.l.])
1 online resource
Keywords: British Assam holds an important place in the history of the British Empire in South Asia. This is especially so in the context of colonial frontier- making. It is in this regard that the book examines what it culturally meant to be a hunter, peasant or rebel between the late nineteenth and mid-twentieth centuries in the British Assam frontier. The book highlights that these figures are of conceptual significance. While the figures were of contrastive nature, the complexity of underlying relations through and in which British colonialism constituted and reproduced itself in Assam could be uncovered from a study of these contrastive figures. Using a wide spectrum of archival sources, the hunters' memoirs, the peasants' ballads and a rebel's worldview are examined as the cultural forms through which one can study these relations that generated the sense of colonial reality in these figures. Through these issues, the book examines what constituted the nature of the British Assam frontier, and how colonialism and capitalism shaped and reproduced an imperial frontier. Part of the Empire and Frontiers book series, this book will be of great interest to students and researchers of history, cultural studies, anthropology, literary studies, frontiers and borderland studies and South Asian studies.